2022
DOI: 10.3390/ijerph19127288
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hyperuricemia with Impaired Left Ventricular Systolic Function in Patients with Atrial Fibrillation and Preserved Kidney Function: Analysis of the POL-AF Registry Cohort

Abstract: Hyperuricemia is associated with the risk of developing atrial fibrillation (AF) and heart failure. However, coexisting chronic kidney disease and certain cardiovascular drugs make it difficult to determine whether hyperuricemia is a risk factor or merely a marker of pathology. We retrieved data from the Polish Atrial Fibrillation (POL-AF) registry, which included consecutive patients hospitalized with AF from January to December, 2019. We included 829 patients (mean age: 72.7 ± 11.1 years) with data on serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Follow‐up time ranged from 1 to 29 years. These studies were conducted in China, 24 , 25 , 26 Poland, 27 Italy, 28 Japan, 29 USA, 30 , 31 , 32 Turkey, 33 and Korea. 34 Heart failure was diagnosed according to ESC guidelines or based on symptoms, physical signs, and treatment response.…”
Section: Resultsmentioning
confidence: 99%
“…Follow‐up time ranged from 1 to 29 years. These studies were conducted in China, 24 , 25 , 26 Poland, 27 Italy, 28 Japan, 29 USA, 30 , 31 , 32 Turkey, 33 and Korea. 34 Heart failure was diagnosed according to ESC guidelines or based on symptoms, physical signs, and treatment response.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the TOPCAT trial included a few patients with non-vitamin K antagonist oral anticoagulants, and further study could examine the impact of non-vitamin K antagonist oral anticoagulants on our results [ 28 ]. In addition, although some studies suggested hyperuricemia as a marker of HFrEF [ 29 ], whether similar results were observed in the HFpEF population needs further examination.…”
Section: Discussionmentioning
confidence: 95%
“…The connection between UA and EF is unaffected by renal function or the use of common HF medicines like diuretics. To predict an EF of less than 40%, 6.69 mg/dL of UA concentration was the cut-off point for higher UA concentrations (17).…”
Section: Atrial Fibrillationmentioning
confidence: 99%